Implementation of Artificial Intelligence (AI) in Evaluating Strategic Decisions Based on Islamic Values - Nadiah Khusnul Khotimah; Fioni Amalia Putri; Lisa Zahara; Muhammad Nur Maulana; Agustina Mutia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Decision-making is an important process in management that involves systematically selecting the best alternative to solve a problem. In the digital era, artificial intelligence (AI) has changed the paradigm of decision-making in companies, especially in marketing, finance, management information systems, and product development. AI enables big data analysis, hidden pattern detection, and automation of processes that previously required human intervention, thereby increasing operational efficiency and innovation. However, the use of AI raises ethical challenges, such as transparency, algorithmic bias, data privacy, and its impact on the workforce. From an Islamic perspective, the application of AI must be in line with sharia principles such as justice ('adl), amanah, maslahah, and shura. AI is seen as a tool (not a substitute) in supporting human duties as caliphs on earth, with use directed to achieve public welfare without violating the boundaries of Islamic ethics and law. Human and AI collaboration in corporate decision-making must be developed holistically with a balanced moral, spiritual, and technological approach to achieve blessings and sustainable welfare (falah).